Descriptive Study: Knowledge, Attitudes, and Hygiene Sanitation Behavior of Food Handlers in Stalls Around the Health Polytechnic of the Ministry of Health Surabaya - Alisa Oriana; Mujayanto Mujayanto; Taufiqurrahman Taufiqurrahman; Ani Intiyati (Journal of Nutrition Explorations, 2025)
Food handlers play an essential role in maintaining food safety and quality through the application of sanitary hygiene principles. Preliminary research showed that sanitary hygiene practices among food handlers in stalls surrounding the Health Polytechnic of the Ministry of Health Surabaya remain relatively low. This study aims to describe the knowledge, attitudes, and behaviors of food handlers regarding sanitary hygiene. A descriptive quantitative design was employed involving 20 respondents. Data were collected through questionnaires and observations, then analyzed univariately. Results showed that the majority of food handlers had moderate knowledge (50%), moderate attitudes (45%), and good behavior (65%). Factors such as age, education, and years of service were found to influence these aspects. In conclusion, most food handlers had moderate levels of knowledge and attitudes, with good hygiene behavior. Continuous education is needed to improve their understanding and practices.